Serological and biochemical relationships between the alleged avirulent variant of Corynebacterium kutscheri and streptococci of group N. - Hirst, R. G. (Cambridge University Press, 1978)
Morphological, biochemical and serological observations suggested that no close relationship existed between C. kutscheri and its alleged avirulent variant isolated from mice at the Rockefeller University. However, both capillary and double diffusion precipitin reactions showed the alleged variant to be a streptococcus of group N, indistinguishable from that previously isolated from Rockefeller University mice.